PROBLEMS AND FEATURES OF DEVELOPMENT OF SMALL AND MEDIUM ENTERPRISES IN IVANO-FRANKIVSK REGION - Rishchuk , L.I. (The actual problems of regional economy development, 2018)
The peculiarities and problems of entrepreneurship development in the region are characterized, because in recent years there has been a tendency to reduce the number of enterprises in the region. The regional target program of entrepreneurship development is described, implementation of which will promote creation of new and development of existing objects of information and infrastructure network of support of entrepreneurship, increase of financial and credit support, involvement of business entities in participation in projects of international technical assistance. The proposals of effective development of small and medium enterprises on the regional level are substantiated.